Increased urinary indoxyl sulfate (indican): New insights into gut dysbiosis in Parkinson's disease. Issue 4 (April 2015) - Cassani, Erica; Barichella, Michela; Cancello, Raffaella; Cavanna, Ferruccio; Iorio, Laura; Cereda, Emanuele; Bolliri, Carlotta; Zampella Maria, Paola; Bianchi, Francesca; Cestaro, Benvenuto; Pezzoli, Gianni
Abstract: Introduction: Changes in the composition of gut microflora have been associated with an increase in chronic diseases. Indican urinary concentration is one of the most common and easily assessable markers of intestinal dysbiosis. Little information is available on intestinal dysbiosis in Parkinson's disease (PD). We decided to investigate indican urinary concentrations in a cohort of PD patients. Methods: A case–control study including PD patients (N = 68) on treatment with levodopa (PD) or on no pharmacological treatment ( De Novo, DPD; N = 34) and an age and gender-matched healthy control group (CTR; N = 50). Main confounders, such as nutritional habits and constipation diagnosed according to Rome III criteria, were also investigated. Results: Indican urinary concentrations were significantly higher in PD and DPD than in CTR (P < 0.001 and P < 0.01, respectively). In PD patients the concentrations were unrelated to the presence of constipation, whereas this symptom was associated with higher concentrations in controls (P = 0.043). The frequency of dairy product consumption was also positively associated with increased concentrations (P = 0.008). Predictors of indican concentrations were sought by multivariate linear regression analysis. The higher indican urinary concentrations found in both DPD (P = 0.045) and PD (P = 0.023) patients persisted after adjustment for age, gender, BMI, constipation and consumption of dairy products. Conclusions: Gut dysbiosis seems to be an important issue in PD, independently of the presence of constipation and starting from the early stages of the disease. The role of gut dysbiosis in the pathogenesis of PD deserves further investigation. Highlights: Growth of gut microbiota results in the release of bacterial metabolism products. Urinary indican allows assessing dysbiosis and small intestinal bacterial overgrowth. Indican concentrations were higher in Parkinson's disease patients than controls. Higher values appeared to be independent of dietary habits and constipation. These findings are indicative of gut dysbiosis in Parkinson's disease patients. Furthermore, dysbiosis seems to be present since the early stages of the disease.